2014
DOI: 10.1017/s1355617714000253
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Emotion Integration in Bipolar Disorder: An Investigation of Involuntary Cross-Modal Influences between Facial and Prosodic Channels

Abstract: The ability to integrate information from different sensory channels is a vital process that serves to facilitate perceptual decoding in times of unimodal ambiguity. Despite its relevance to psychosocial functioning, multimodal integration of emotional information across facial and prosodic modes has not been addressed in bipolar disorder (BD). In light of this paucity of research we investigated multimodal processing in a BD cohort using a focused attention paradigm. Fifty BD patients and 52 healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 51 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Indeed, BD patients do evidence deficits across a number of cognitive and emotional processes (e.g., Rossell et al, , 2014Van Rheenen and Rossell, 2013, 2014a, 2014b, 2014c, of which many may not be instrumental to the disorder's cause but might rather represent outcomes secondary to BD itself. This may not be the case here, given that the different pattern of associations with trait mania found within the BD group compared to controls suggests a fundamental change in emotion regulation during BD, which may partially underlie its clinical phenotype.…”
Section: Predictorsmentioning
confidence: 99%
“…Indeed, BD patients do evidence deficits across a number of cognitive and emotional processes (e.g., Rossell et al, , 2014Van Rheenen and Rossell, 2013, 2014a, 2014b, 2014c, of which many may not be instrumental to the disorder's cause but might rather represent outcomes secondary to BD itself. This may not be the case here, given that the different pattern of associations with trait mania found within the BD group compared to controls suggests a fundamental change in emotion regulation during BD, which may partially underlie its clinical phenotype.…”
Section: Predictorsmentioning
confidence: 99%
“…The underlying neurocognitive processes that integrate separate streams of information from different sensory channels into the overall experience are often referred to as multisensory integration (MSI) ( 23 ). Researchers focused on healthy adults ( 18 ), patients with bipolar disorder ( 24 ), and patients with schizophrenia ( 25 , 26 ) showed that multisensory integration of emotional cues is beneficial because the integration of information from multiple channels will increase the recognition speed and hit rate of emotional information.…”
Section: Introductionmentioning
confidence: 99%
“…Emotional information and perception in natural environments are rarely based on only one sensory modality (De Gelder & Bertelson, 2003). In daily life, the emotional stimulation of several sensory modalities often occurs simultaneously, and the cross-modal emotional influences between different sensory channels are thought to be strong (Van Rheenen & Rossell, 2014). This multimodal emotional integration is responsible for enriching perception, compensating for conflicts in cross-modal sensation and facilitating perceptual decoding in times of unimodal ambiguity (De Gelder & Bertelson, 2003;Dolan, Morris, & De Gelder, 2001;Pourtois, Gelder, Bol, & Crommelinck, 2005).…”
Section: Introductionmentioning
confidence: 99%